can brainly solve it? I don't need answer.. explain it...
Attachments:
![](https://hi-static.z-dn.net/files/dab/7aea19c5850c9b6d04a7ac8661864449.jpg)
Answers
Answered by
0
It depend upon the users of brainly how they answer to this question....!
I think that brainly can solve it
I think that brainly can solve it
Answered by
1
Given: tan^-1 x + cot^- 1 x
Let A = tan^-1 x.
x = tan A
Now,
A + cot^-1 x
A + cot^-1(tan A)
![A + cot^{-1}(cot( \frac{ \pi }{2} - A)) A + cot^{-1}(cot( \frac{ \pi }{2} - A))](https://tex.z-dn.net/?f=A+%2B++cot%5E%7B-1%7D%28cot%28+%5Cfrac%7B+%5Cpi+%7D%7B2%7D+-+A%29%29)
We know that cot^-1(cot x) = x
![A + \frac{ \pi }{2} - A A + \frac{ \pi }{2} - A](https://tex.z-dn.net/?f=A+%2B+++%5Cfrac%7B+%5Cpi+%7D%7B2%7D+-+A)
![\frac{ \pi }{2} \frac{ \pi }{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B+%5Cpi+%7D%7B2%7D+)
Hope this helps!
Let A = tan^-1 x.
x = tan A
Now,
A + cot^-1 x
A + cot^-1(tan A)
We know that cot^-1(cot x) = x
Hope this helps!
siddhartharao77:
:-)
Similar questions